A descriptive study of affixation in Chinese and Indonesian and their morphological types - Marlim, Yenny (Indonesian Journal of Applied Linguistics, 2024)
The comparison of language systems in different language families is still a topic worth in-depth research. Both Chinese and Indonesian are languages with large population in the world, belonging to the language families of Sino-Tibetan and Austronesian, respectively. However, the comparison of their morphologies has received less attention, and scholars hold different views on their morphological types. This study delves into the types of affixation in Chinese and Indonesian, analysing their similarities and differences to deepen our understanding of the basic morphological types in both languages. Descriptive qualitative approach, current literature and document analysis are the main research method applied in this study. The findings reveal that Chinese and Indonesian affixes are mainly derivational, both have sound changes and the same mechanism of borrowed affixes. However, both Chinese and Indonesian exhibit unique types of affixation, varying in the number of allomorphs and the patterns of sound changes across different affixes; some Chinese affixes can be a root, and some of their quasi affixes are expressed in a free word in Indonesian. Analysing the morphological process of affixation in Chinese and Indonesian can further elucidate their basic morphological types. Chinese is a typical isolating language, but its affixes have certain characteristics of agglutinating language. Indonesian can be regarded as an isolating language in which its affixes have abundant characteristics of agglutinating language.